2020
DOI: 10.3390/ijerph17072364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Double-Taped Kinesio Taping on Pain and Functional Performance due to Muscle Fatigue in Young Males: A Randomized Controlled Trial

Abstract: Kinesio taping (KT) is widely applied for pain control and rehabilitation in clinical settings. Tape tension is a key factor in the taping method. However, limited evidence exists regarding the reinforced tension effects of KT on functional performance and pain in healthy individuals. This study aimed to investigate the immediate effects of double-taped Kinesio taping (DTKT) on functional performance and pain caused by muscle fatigue after exercise. A total of 44 healthy male students (mean age, 23.3 ± 2.2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
11
0
2
Order By: Relevance
“…Twenty-two studies investigated the effects of Kinesio taping on jump performance measured as jump distance, height, flight time, execution time, power, velocity, impact, stiffness and rate of force development, in three populations. 26,28,30,33,39,40,52,55,59,63,67,70 –80 Meta-analyses were carried out for healthy people and people with chronic ankle instability.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies investigated the effects of Kinesio taping on jump performance measured as jump distance, height, flight time, execution time, power, velocity, impact, stiffness and rate of force development, in three populations. 26,28,30,33,39,40,52,55,59,63,67,70 –80 Meta-analyses were carried out for healthy people and people with chronic ankle instability.…”
Section: Resultsmentioning
confidence: 99%
“…Kinesio taping was introduced by Kenzo Kase as a method of attaching an elastic adhesive tape with elasticity similar to that of the skin and is currently used in rehabilitation for various purposes [11]. Taping is applied in combination with other therapeutic techniques to strengthen weakened muscles, regulate joint instability, assist postural alignment, reduce pain, improve blood flow and lymphatic circulation, relieve spasticity, and strengthen muscle function [12][13][14]. Additionally, studies have reported that pelvic inclination decreases when taping is applied for posture correction [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were evaluated before and one day after the final intervention by three well-trained physical therapists, who did not have any information on the subjects and the purpose of this study. The 100-mm VAS was used to measure the degree of pain, and it is a clinical tool that is widely used to measure subjective pain in the clinic and in researches [ 10 , 14 , 21 ]. The VAS subjectively displays the pain intensity that the patient feels by using a 100-mm horizontal line marked from 0 to 100 from left to right, with 0 meaning no pain and 100 meaning maximum pain.…”
Section: Methodsmentioning
confidence: 99%
“…However in the past 20 years, various application methods and physiological effects of taping have been reported in various types of patients and subjects. According to the previous studies, taping methods show positive effects on the alleviation of pain caused by muscle fatigue [10], the increase of gait and balance function in strokes [11,12], and the management of pain and functional disability in patients with epicondylitis [13], wrist pain [14], and hand osteoarthritis [15]. Interestingly, however, some studies reported that therapeutic exercise combined with taping improves pain relief and motor function more effectively than exercise only [11,13].…”
Section: Introductionmentioning
confidence: 99%